Art Futura 93. : Vida Artificial. - Art Futura Barcelona 1993 (Barcelona : Art Futura, 1993)
Berenguer, Xavier ; Sims, Karl ; Latham, William ; Ninio, Jacques ; Stelarc ; Dougherty, Peter ; Mariscal ; Vivar, Hipolito ; Giménez Noguera, Josep ; Babiole, Cécile ; Xaos ; Gabriel, Peter ; Johnson, Stephen ; M. Thalmann, Nadia
Art Futura, Barcelona, 22-24 Abril, 1993
boek